2017
DOI: 10.1063/1.4994898
|View full text |Cite
|
Sign up to set email alerts
|

From isolated diamondoids to a van-der-Waals crystal: A theoretical and experimental analysis of a trishomocubane and a diamantane dimer in the gas and solid phase

Abstract: The electronic properties of sp/sp diamondoids in the crystalline state and in the gas phase are presented. Apparent differences in electronic properties experimentally observed by resonance Raman spectroscopy in the crystalline/gas phase and absorption measurements in the gas phase were investigated by density functional theory computations. Due to a reorganization of the molecular orbitals in the crystalline phase, the HOMO (highest occupied molecular orbital) and LUMO (lowest unoccupied molecular orbital) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Based on the geometries from ref , we optimized the cell parameters and atomic positions of all systems until cell stress and interatomic forces were below 0.01 GPa and 0.01 eV/Å, respectively. Comparable to refs , , we assumed that the measured diamondoid compounds form van der Waals crystals. Noncovalent interactions were included through adaptive dispersion corrections from the D3­(BJ) method .…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
“…Based on the geometries from ref , we optimized the cell parameters and atomic positions of all systems until cell stress and interatomic forces were below 0.01 GPa and 0.01 eV/Å, respectively. Comparable to refs , , we assumed that the measured diamondoid compounds form van der Waals crystals. Noncovalent interactions were included through adaptive dispersion corrections from the D3­(BJ) method .…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
“…[9] Further,p recise crystal engineering of tert-butylated triptycene derivatives showeda lso very close tBu-tBu interactions in the solid state. [14] By means of gas-phase experiments, [15][16][17][18] molecular balance studies, [8,[19][20][21][22][23][24][25][26][27] andadvances in computationalmethodologies, [4,28,29] the view on London dispersion clearly changed during the last decade. [2,30] The scientific community realized how nature is taking advantage of these interactions for the assembly of large architectures.…”
Section: Introductionmentioning
confidence: 99%
“…The single-bond dimers can be further clearly distinguished from sp 2 −bound dimers, as the latter show the characteristic C=C vibrations at ∼ 1660 cm −1 . 18,23,24 All remaining dimer modes have only very low Raman intensities both in the computations and experiments and can thus not be identified in the Raman spectra.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the optical absorption energies can be tuned considerably by various functionalizations [16][17][18][19][20][21] . It was shown that the insertion of sp 2 defects as an interconnecting bridge between diamondoid monomers reduces the optical transition energies by ∼ 2 eV 18,20,[22][23][24][25][26] . Such chemically blended diamondoids further exhibit vibrational properties characteristic for both the sp 2 and sp 3 diamondoid moieties 18,23,24,[26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation